Long‐term outcomes of eculizumab‐treated positive crossmatch recipients: Allograft survival, histologic findings, and natural history of the donor‐specific antibodies. Issue 6 (15th December 2018) - Schinstock, Carrie A.; Bentall, Andrew J.; Smith, Byron H.; Cornell, Lynn D.; Everly, Matthew; Gandhi, Manish J.; Stegall, Mark D.
Abstract : We aimed to determine the long‐term outcomes of eculizumab‐treated, positive crossmatch (+XM) kidney transplant recipients compared with +XM and age‐matched negative crossmatch (−XM) controls. We performed an observational retrospective study and examined allograft survival, histologic findings, long‐term B‐cell flow cytometric XM (BFXM), and allograft‐loss–associated factors. The mean (SD) posttransplant follow‐up was 6.3 (2.5) years in the eculizumab group; 7.6 (3.5), +XM control group; 7.9 (2.5), −XM control group. The overall and death‐censored allograft survival rates were similar in +XM groups ( P  =   .73, P  =   .48) but reduced compared with −XM control patients ( P  <   .001, P  <   .001). In the eculizumab‐treated group, 57.9% (11/19) of the allografts had chronic antibody‐mediated rejection, but death‐censored allograft survival was 76.6%, 5 years; 75.4%, 7 years. Baseline IgG3 positivity and BFXM ≥300 were associated with allograft loss. C1q positivity was also associated with allograft loss but did not reach statistical significance. Donor‐specific antibodies appeared to decrease in eculizumab‐treated patients. After excluding patients with posttransplant plasmapheresis, 42.3% (9/21) had negative BFXMs; 31.8% (7/22), completely negative single‐antigen beads 1 year posttransplant. Eculizumab‐treated +XM patients had reduced allograft survival compared with −XM controls but similar survival to +XM controls. BFXM and complement‐activating donor‐specific antibodies (by IgG3 and C1q testing) may be used for risk stratification in +XM transplantation. Abstract : The authors present the long‐term allograft histology, alloantibody, and death‐censored allograft survival data for eculizumab‐treated positive crossmatch kidney transplant recipients. See Loupy et al's editorial on page1611 .